ENT Mentorship Program for Preclinical Medical Students. (August 2020) - Sethia, Rishabh; Sheehan, Cameron C.; Danforth, Douglas; Essig, Garth; Teknos, Theodoros N.; Elmaraghy, Charles A.
Objective: To provide preclinical medical students early access to otolaryngologists to learn about the specialty, facilitate acquisition of clinical skills, and provide one-on-one mentorship. Methods: Students are matched with a single otolaryngology faculty mentor from The Ohio State University/Nationwide Children's Hospital and attend 8 hours per month in the clinic or operating room, monthly lectures, and rounds, and they give a final presentation. Mentors complete performance evaluations, and surveys are administered longitudinally until Match Day. Results: Thirty-five students and 17 faculty members have participated in the program since 2015. All mentors and students found the program to be a valuable experience. When compared to nonparticipating students, participants had significantly higher confidence scores for clinical performance, knowledge of anatomy, and familiarity with the department of interest. All students felt the program prepared them well for third and fourth years, and all 8 of the initial program participants successfully matched into residency with 4 entering otolaryngology. Discussion: Medical students face a competitive residency application process in otolaryngology with limited exposure, which creates an opportunity for guidance in the pursuit of matching into this field. This novel preclinical mentorship program prepares students for their clinical years and residency by facilitating acquisition of various competencies. Students gain hands-on clinical exposure in a field of interest and support for navigating the application process. Implications for Practice: The structure of this program can be applied to other medical schools or specialties if the individual departments contain adequate resources of teaching faculty willing to participate.